Design and Development of an Oxygen Generator System - sharrad, Kadhlm Hamza; Thajeel, Ahmed Abdullah; Razaq, Ali Adel; Ghazi, Hussein Ali (American Journal of Botany and Bioengineering, 2024)
Some people suffer from healthy problems concerning breathing difficulties, so that it could be hard to take them continuously to the hospital or health facilities. In addition, those who have chronic diseases especially with our polluted atmosphere and dusty, unexpected weather. For that, we design a system to generate Oxygen, and this system is can be easily moved and it is makeable as portable machine. This device design as continence to the patient. Therefore, it can be easily existed and available at home. In addition, it is smoothly movable. We show perfect results that could help the patient and reduce his fatigue to transfer from place to other. Getting the oxygen percentage, which is, should be 90- 91%. This is very good percentage. Moreover, the device consists of the compressor, A compressed air dryer, Filters٫ Valves٫ Regulator٫ Oxygen tank٫ The generator٫ Flow meter, Stan.